2022
DOI: 10.20517/2574-1225.2021.137
|View full text |Cite
|
Sign up to set email alerts
|

Revisional bariatric surgery for chronic complications necessitates custom surgical solutions

Abstract: Bariatric surgery continues to grow as a treatment modality for obesity and weight-related comorbidities. The anatomic rearrangement can produce unique anatomic complications, as well as functional problems that are correctible with revisional operations. Understanding the unique subset of complications and the options available for correction can allow surgical solutions to be tailored to both the patient’s anatomy, and the symptoms or pathologies they are targeting. Revisional operations are becoming increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…American Society of Metabolic and Bariatric Surgeons (ASMBS) data, has reported that the proportion of revisional bariatric procedures performed in the United States increased from 6 % to 16.7 % between 2011 and 2019 [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…American Society of Metabolic and Bariatric Surgeons (ASMBS) data, has reported that the proportion of revisional bariatric procedures performed in the United States increased from 6 % to 16.7 % between 2011 and 2019 [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversion to an open approach is frequently required, as surgeries are technically demanding due to severe adhesions and/or distorted anatomy. However, they can be executed safely in experienced centers, with mortality and morbidity similar to a primary approach [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, Revisional Bariatric Surgery (RBS) compose 9-18% of all MBS [2][3][4]. The main indications for RBS are weight regain (WR) or insufficient weight loss (IWL)and 10-50% of patients with a previous restrictive procedure may require RBS [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Longer operative times and length of hospital stay, greater blood loss and risk for Intensive Care Unit stay, and more postoperative complications, readmissions, and reoperations have been reported for revisional procedures [ 18 ]. However, RMBS can be safely performed with acceptable outcomes in most cases [ 19 ], when performed by experienced bariatric surgeons in bariatric centers that have the resources to manage possible complications [ 20 ].…”
Section: Introductionmentioning
confidence: 99%